On the Influence of the Current Feedback to the Atmosphere on the Western Mediterranean Sea Dynamics. Issue 1 (15th January 2021) - Renault, L.; Arsouze, T.; Ballabrera‐Poy, J.
Abstract: The ocean Current FeedBack to the atmosphere (CFB) has been shown to be an unambiguous physical process to achieve proper equilibrium in the Ocean. However, its effects on the Western Mediterranean Sea (WMS) are not known. In this study, eddy‐rich coupled ocean‐atmosphere simulations are carried out for the WMS to assess the extent to which CFB alters the WMS circulation and to characterize the low‐level wind and surface stress responses to CFB. By generating conduits of energy from oceanic currents to the atmosphere, CFB slows the mean circulation by about 10% and acts as an oceanic eddy killer, reducing the mesoscale activity by 25% and attenuating the intensity of their intermittency. It also alters the mean barotropic vorticity balance of the WMS Gyre, reducing the role of wind stress curl, nonlinear torque, and bottom pressure torque. By reducing the eddy‐mean flow interaction, CFB has a large influence on the properties of the Algerian Current, reducing the presence of standing eddies near Sardinia and improving the realism of the circulation. It also modifies the Alboran Gyres formation and the Northern Current retroflection. Finally, coupling coefficients from the coupled simulations are estimated and are consistent with those for other regions. The CFB coupling coefficients can be used to parameterize the CFB in a forced ocean model. Overall, our results show that, as for other regions, the CFB is another physical mechanism to be considered for the representation of the WMS circulation. Plain Language Summary: The ocean Current FeedBack to the atmosphere (CFB) is the influence of the surface currents on the surface stress and wind. In the recent years, it has been shown to be a unambiguous physical process to achieve proper equilibrium in the Ocean. However its effects on the Western Mediterranean Sea (WMS) are not known. In this study, eddy‐rich coupled ocean‐atmosphere simulations are carried out for the WMS to assess the extent to which CFB alters the WMS circulation and to characterize the low‐level wind and surface stress responses to CFB. We show that CFB induces conduits of energy from oceanic currents to the atmosphere, which in turn slow down the mean circulation by about 10% and damp the intermittency of the currents by 25%. CFB alters processes that controls the WMS circulation and largely modulates emblemactics features of the WMS such as the Alboran Gyres and the Algerian Current. Finally, coupling coefficients are estimated and are consistent with those for other regions. The CFB coupling coefficients can be used to parameterize the CFB in a forced ocean model. Overall, our results show that the CFB is another physical mechanism to be considered for the representation of the WMS circulation. Key Points: Current feedback, as a physical process, slows down the Western Mediterranean Sea Circulation and reduces the intermittency of the currents It affects the mean barotropic vorticity budget and weakens the eddy‐mean flow interaction It alters key features of the Western Mediterranean Sea Circulation, such as the Alboran Gyres and the Algerian Current